Relationship between smoking and pulmonary tuberculosis based on positive sputum smears - Shinde, Mahesh; Dixit, Sangramsingh; Patel, Mihir; Sharma, Atharva; Satam, Juily; Patil, Yogeshwari; Upadhyay, Dheer; Chiwadshetti, Shreyasi; Mathur, Adhiraj; Rege, Varad; Kumari, Arunojya; Seth, Hiya (German Medical Science GMS Publishing House, 2024)
Introduction: Smoking and tuberculosis are the two major, global health problems. Not only active smokers but also passive smokers are at risk of becoming infected with tuberculosis. Through many mechanisms, smoking decreases immunity and predisposes to numerous infections. This has a negative impact on our health system. This knowledge of the association between smoking and tuberculosis can be utilized to develop a program for TB prevention and control.Method: This is a retrospective observational study carried out over a period of 18 months on 100 diagnosed cases of sputum smear-positive pulmonary tuberculosis patients undergoing treatment at Mumbai Maharashtra India as a part of the Revised National Tuberculosis Control Program (RNTCP).Results: 1+ sputum positivity was observed in a higher number of nonsmokers (77%) followed by ex-smokers (43%) and smokers (2%), 2 3+ sputum positivity was observed in a higher number of smokers (63% and 35%, respectively) followed by ex-smokers (29%) and nonsmokers (18% and 5%, respectively). Conclusion: Smokers demonstrated extensive infiltrates as compared to nonsmokers. Additionally, as the severity of smoking increased (smoking index), and the bacterial load also increased (higher grades of sputum positivity). Smokers also had poorer treatment outcomes than did nonsmokers.